Sustainability Status of Small-Scale Tuna Fisheries Based on the Ecosystem Approach to Fisheries Management - Taufan Setyono; James Edward Collins; Nayafadila (Journal of Marine Fisheries, 2026)
Small-scale tuna fisheries play a critical role in food security and coastal livelihoods in Indonesia. However, increasing fishing pressure, habitat degradation, and weak governance threaten their sustainability. This study aims to analyze the sustainability status of small-scale tuna fisheries using the Ecosystem Approach to Fisheries Management (EAFM). The research applies a systematic literature review of 50 scientific sources covering ecological, economic, social, and institutional dimensions. The results show that most fisheries are classified as moderately sustainable, while some areas demonstrate good ecological conditions and a smaller portion show poor sustainability status. Ecological performance is identified as the most sensitive dimension, particularly influenced by fish size reduction, habitat pressure, and Fish Aggregating Devices (FADs) usage. Institutional weakness and inconsistent enforcement further limit sustainability outcomes. Economic conditions vary across regions, with income instability affecting fishers’ resilience. The study concludes that strengthening ecosystem-based governance, improving monitoring systems, and controlling fishing effort are essential to ensure long-term sustainability of small-scale tuna fisheries in Indonesia.